2018
DOI: 10.1002/mgg3.515
|View full text |Cite
|
Sign up to set email alerts
|

Gene coexpression network analysis identified potential biomarkers in gestational diabetes mellitus progression

Abstract: Background Gestational diabetes mellitus (GDM) is one of the most common problems during pregnancy. Lack of international consistent diagnostic procedures has limit improvement of current therapeutic effectiveness. Here, we aimed to screen potential gene biomarkers that might play vital roles in GDM progression for assistance of its diagnostic and treatment. Methods Gene expression profiles in four GDM placentae at first trimester, four GDM placentae at second trimester, and four normal placentae were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…AURKB promotes survival of cancer cells by cell cycle progression with phosphorylating a series of downstream substrates, including RacGAP1 . A study of gene coexpression network analysis identified that AURKB might be valuable biomarkers of gestational diabetes mellitus (Zhao and Li, 2019). Our results of the network pharmacology analysis also revealed that AURKB was targeted by eight components in SKP and interacted with many other proteins.…”
Section: Discussionsupporting
confidence: 58%
“…AURKB promotes survival of cancer cells by cell cycle progression with phosphorylating a series of downstream substrates, including RacGAP1 . A study of gene coexpression network analysis identified that AURKB might be valuable biomarkers of gestational diabetes mellitus (Zhao and Li, 2019). Our results of the network pharmacology analysis also revealed that AURKB was targeted by eight components in SKP and interacted with many other proteins.…”
Section: Discussionsupporting
confidence: 58%
“…A study by Deyssenroth et al 26 based on 200 placenta samples observed 17 modules, while another study by Buckberry et al based on 16 samples observed 13 modules. 27 Two other studies used microarray data: 33 modules reported by Zhao et al 28 after analysis of a previously deposited dataset of 16 samples; 17 modules reported by Cox et al 29 These differences in the number of modules reported across these studies maybe driven by study considerations (sample size, platform, etc) as well as true complexity in placental gene activity. The number of modules identified in our study falls within the range reported in the literature, and the enriched pathways are consistent with what are previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…As with hPL, the observed results may be because the proposed changes in hormone synthesis are not evident in the term placenta. Recent findings have demonstrated, via gene set enrichment analysis, that GDM placental gene expression profiles from the first and second trimesters of pregnancy had a significant upregulation of steroidogenic pathways (Zhao & Li, 2019). Additionally, elevated plasma progesterone levels have been reported during the second trimester in women who developed GDM (Ngala et al .…”
Section: Discussionmentioning
confidence: 99%